Russian Federation : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents key findings of the Financial System Stability Assessment for the Russian Federation. There are significant vulnerabilities and weaknesses in the financial sector, although given its small size, the macroeconomy would be relatively little affected by the immediate impact of any financial sector distress. Several interlinked issues cut across the banking, capital markets, and insurance sectors and contribute to the identified vulnerabilities. According to official data, banks are in general well capitalized, but the quality of capital is questionable, and loan loss provisioning may not fully reflect risks.